Unraveling the Microbial Symphony: Impact of Antibiotics and Probiotics on Infant Gut Ecology and Antibiotic Resistance in the First Six Months of Life - Qi Qi; Liang Wang; Yingze Zhu; Shaoru Li; Mitslal Abrha Gebremedhin; Baozhu Wang; Zhonghai Zhu; Lingxia Zeng (MDPI AG, 2024)
We aimed to examine the effects of antibiotic and probiotic usage on the gut microbiota structure and the presence of antibiotic-resistance genes (ARGs) in infants during the first six months of life. Questionnaires and fecal samples were collected within three days of birth, two months, and six months to assess antibiotic and probiotic exposure. Gut microbiotas were sequenced via 16S rRNA, and ARGs were conducted by qPCR, including beta-lactam (mecA, blaTEM), tetracycline (tetM), fluoroquinolone (qnrS), aminoglycoside (aac(6')-Ib), and macrolide (ermB). Infants were categorized by antibiotic and probiotic usage and stratified by delivery mode, microbial composition, and ARG abundances were compared, and potential correlations were explored. A total of 189 fecal samples were analyzed in this study. The gut microbiota diversity (Chao1 index) was significantly lower in the "only probiotics" (PRO) group compared to the "neither antibiotics nor probiotics" (CON) group at six months for the CS stratification (p = 0.029). Compositionally, the abundance of core genus Bifidobacterium_pseudocatenulatum was less abundant for the antibiotic during delivery (IAP) group than that in the CON group within the first three days (p = 0.009), while core genus Enterococcus_faecium was more abundant in the PRO than that in the CON group (p = 0.021) at two months. ARGs were highly detected, with Enterococcus hosting tetM and Escherichia associated with blaTEM within three days of birth, though no correlation was found between Bifidobacterium and ARGs. These findings emphasized the critical importance of carefully managing antibiotic and probiotic exposures in early life, with implications for promoting lifelong health through preserving a healthy infant gut ecosystem.